2002
DOI: 10.1289/ehp.02110s5729
|View full text |Cite
|
Sign up to set email alerts
|

Reductive activation with cysteine represents a chromium(III)-dependent pathway in the induction of genotoxicity by carcinogenic chromium(VI).

Abstract: Induction of DNA damage by carcinogenic hexavalent chromium compounds [Cr(VI)] results from its reduction to lower oxidation states. Reductive metabolism of Cr(VI) generates intermediate Cr(V/IV)species, organic radicals, and finally Cr(III), which forms stable complexes with many biological ligands, including DNA. To determine the biological significance of different reaction products, we examined genotoxic responses and the formation of DNA damage during reduction of Cr(VI) by its biological reducer, cystein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…Although epidemiological studies have not found a connection between chromium (VI) exposure and cancer incidence in residential populations, positive associations between chromium exposure and cancers of the digestive tract were reported among workers exposed to high levels of chromium (VI) [Proctor et al, 2002]. Several reports demonstrate that chromium (VI) is metabolized to a carcinogenic derivative by forming stable complexes with biological ligands like DNA [Zhitkovich et al, 2002], and systemic absorpEnvironmental and Molecular Mutagenesis. DOI 10.1002/em tion and increases in the rate of cancer have been observed in people chronically exposed above the permissible limits [IARC, 1990].…”
Section: Discussionmentioning
confidence: 99%
“…Although epidemiological studies have not found a connection between chromium (VI) exposure and cancer incidence in residential populations, positive associations between chromium exposure and cancers of the digestive tract were reported among workers exposed to high levels of chromium (VI) [Proctor et al, 2002]. Several reports demonstrate that chromium (VI) is metabolized to a carcinogenic derivative by forming stable complexes with biological ligands like DNA [Zhitkovich et al, 2002], and systemic absorpEnvironmental and Molecular Mutagenesis. DOI 10.1002/em tion and increases in the rate of cancer have been observed in people chronically exposed above the permissible limits [IARC, 1990].…”
Section: Discussionmentioning
confidence: 99%
“…Cr(III) has been shown to interact directly with DNA and other macromolecules to induce chromosomal alterations and mutational changes in DNA as a consequence of DNA adduct formation (Zhitkovich et al 2001(Zhitkovich et al , 2002Quievryn et al 2003;Reynolds et al 2007). Cr(III) forms both binary and ternary DNA adducts (O'Brien, Ceryak, and Patierno 2003;Zhitkovich 2005), with FIGURE 7.-Comparison of total chromium (Cr; mg Cr/g tissue) in red blood cells (RBCs), liver, kidney, and glandular stomach (GS) of male rats (left) and female mice (right) after 182 days of ingestion of similar time-weighted average daily doses of Cr(III) (resulting from exposure in feed to 2,000 ppm chromium picolinate monohydrate [CPM]) and Cr(VI) (resulting from exposure in drinking water to 516 mg sodium dichromate dihydrate (SDD)/L).…”
Section: Mechanisms Of Genotoxicitymentioning
confidence: 99%
“…Hexavalent chromium is transported into the cell via non-specifi c anion transport systems (3,4), where it converts to trivalent chromium (Cr III ), whose highest levels have been reported in the kidney, liver, spleen, and bones (5). Although cytotoxic mechanisms are not exactly understood, several studies have showed that Cr VI induces oxidative stress, DNA damage, single-and double-strand breaks, and affects survival signalling pathways (6)(7)(8). This damage and molecular events are believed to be induced by free radicals (HO˚-and R˚) produced during chromium oxidation/reduction (9).…”
mentioning
confidence: 99%